Organisational Effectiveness in Resource-Constrained Public Safety Institutions: A Diagnostic Analysis Using Weisbord's Six-Box Model in Ghana National Fire Service - Asamane, Lydia-Bonnie; Alhassan, Ibrahim (Advances in Social Sciences Research Journal, 2025)
This study evaluated organizational effectiveness within the Ghana National Fire Service (GNFS) in Sagnarigu Municipal, Northern Region, addressing a research gap where technical capabilities often overshadow organizational factors in fire service literature. Employing Weisbord's Six-Box diagnostic model within a participatory action research framework, the study implemented targeted interventions to enhance organizational effectiveness. A mixed-methods approach was utilized, collecting data from 50 GNFS personnel through an Organizational Capacity Assessment Tool, supplemented by focus groups, interviews, observations, and document analysis. Interventions were collaboratively designed and implemented over a three-month period. The findings revealed varying levels of effectiveness across organizational dimensions. Purpose (1.3) and structure (1.5) emerged as strengths, characterized by a clear understanding of the mission and well-defined reporting relationships. However, rewards (3.5), helpful mechanisms (3.2), and leadership (2.7) presented significant challenges, particularly in terms of resource adequacy and recognition systems. Following the interventions, measurable improvements were observed: rewards improved to 2.8, helpful mechanisms to 2.6, and leadership to 2.2. Qualitative data indicated enhanced transparency, improved resource utilization, and increased staff consultation in decision-making. The research demonstrates that internal organizational factors significantly impact the effectiveness of fire services in fulfilling public safety mandates. The participatory approach facilitated both accurate diagnosis and committed improvement actions despite resource constraints. These findings have important implications for fire service policy and management in developing countries, where maximizing organizational effectiveness is crucial for delivering critical services with limited resources. Future research should explore the relationships between organizational effectiveness and operational performance across multiple stations.